2016
DOI: 10.1016/j.redox.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cells have decreased ability to metabolize H2O2: Implications for pharmacological ascorbate in cancer therapy

Abstract: Ascorbate (AscH−) functions as a versatile reducing agent. At pharmacological doses (P-AscH−; [plasma AscH−] ≥≈20 mM), achievable through intravenous delivery, oxidation of P-AscH− can produce a high flux of H2O2 in tumors. Catalase is the major enzyme for detoxifying high concentrations of H2O2. We hypothesize that sensitivity of tumor cells to P-AscH− compared to normal cells is due to their lower capacity to metabolize H2O2. Rate constants for removal of H2O2 (kcell) and catalase activities were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
257
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 253 publications
(271 citation statements)
references
References 62 publications
12
257
0
2
Order By: Relevance
“…Furthermore, certain tumor cells have been found to be susceptible to H 2 O 2 toxicity [48]. Our present study clearly shows that ascorbic acid significantly increased (>75-fold) TPT cytotoxicity in MCF-7 breast cancer cells, and it was synergistic at all concentrations of TPT, especially at lower and biologically more relevant concentrations of TPT.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, certain tumor cells have been found to be susceptible to H 2 O 2 toxicity [48]. Our present study clearly shows that ascorbic acid significantly increased (>75-fold) TPT cytotoxicity in MCF-7 breast cancer cells, and it was synergistic at all concentrations of TPT, especially at lower and biologically more relevant concentrations of TPT.…”
Section: Discussionsupporting
confidence: 68%
“…The 5-year survival rate for localized RC is 90%; however, as RC spreads to regional lymph nodes or distant parts of the body, the 5-year survival rate drops to between 71% and 13% in the United States [1]. These malignancies are ascribed to accumulation of protein alterations, including dissemination of proto-oncogenes and loss or inactivation of tumor suppressor genes, which ultimately lead to tumor evolution and progression [2-6]. Furthermore, the increased survival and invasiveness of tumor cells are typical characteristics of RC [7, 8], suggesting a clinical need to abate excessive RC cell survival and migration.…”
Section: Introductionmentioning
confidence: 99%
“…Note that figures display P-AscH − dose in both molarity and on a mole cell − 1 basis. Recent studies have demonstrated that specifying the dose of xenobiotics, including P-AscH − , on a “mole per cell” basis results in improved correlations with toxicity markers as well as greater information content in experimental data [28, 29]. The doubling time of MIA PaCa-2 cells treated with P-AscH − was 59 ± 5 h versus 43 ± 0.2 h (means ± SEM, n = 3, p < 0.05) for controls when treated with the ED 50 dose, 7 mM (7 pmol cell − 1 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…P-AscH − will increase extracellular H 2 O 2 , which is transported across the plasma membrane into cancer cells [18, 29, 34]. To determine whether the P-AscH − -induced HIF-1α suppression, VEGF suppression, and decreased clonogenic survival in hypoxia were due to H 2 O 2 , cells were co-treated with catalase (100 U/mL in the culture medium) or transfected with either a control adenoviral vector, AdGFP (50 MOI), or the adenoviral vector containing the catalase gene, AdCat (50 MOI), to increase intracellular catalase activity.…”
Section: Resultsmentioning
confidence: 99%